Comprehensive Analysis of Pedestrian Facilities in Citywalk Tegal City Using Global Walkability Index: A Comparative Assessment and Correlation Study - Agung Budi Dharmawan; Riska Dwi Anjani; Suprapto Hadi; Hanendyo Putro; Ahmad Basuki (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Pedestrian facilities serve as critical infrastructure in promoting sustainable urban mobility and reducing carbon emissions in modern cities. However, pedestrian lanes in Ahmad Yani Street, Tegal City face significant challenges including misuse for non-pedestrian activities such as unauthorized parking and informal trading, which compromises their primary function and safety standards. The study purpose was to conduct a comprehensive evaluation of pedestrian facility quality using the Global Walkability Index (GWI) methodology, establish correlational relationships between infrastructure parameters, compare performance across different street segments, and provide evidence-based improvement recommendations for Ahmad Yani Citywalk Street pedestrian infrastructure in Tegal City. This research employed a mixed-method approach combining systematic field observation surveys and structured questionnaires administered to 75 randomly selected respondents aged over 17 years. The evaluation utilized nine standardized GWI parameters assessed through a validated 1-5 Likert scale, with each parameter calibrated using established weighting coefficients. The research location encompassed Ahmad Yani Citywalk Street, spanning 700 meters and strategically divided into four analytical segments (Normal 1, Normal 2, Opposite 1, Opposite 2) to enable comprehensive comparative analysis. Statistical analysis included correlation coefficient calculations, variance analysis, and comparative performance assessments between segments. The comprehensive analysis revealed an average GWI score of 70.25, positioning the area within the